Controlling Factors of Historical Variation of Winter Tibetan Plateau Snow Cover Revealed by Large‐Ensemble Experiments. Issue 21 (1st November 2021) - Li, Shixue; Sato, Tomonori; Nakamura, Tetsu; Liu, Xiaoyue; Guo, Wenkai
Abstract: This study investigated the factors controlling the interannual variability of Tibetan Plateau snow cover (TPSC) in winter using large‐ensemble simulations. Composite analysis reveals that years with high TPSC are associated with a positive Arctic Oscillation (AO)‐like pattern in which a strengthened subtropical westerly enhances zonal water vapor flux, resulting in greater precipitation over the Tibetan Plateau. Observations and simulations commonly show that TPSC tends to be high during the positive phase of AO, and vice versa. Meanwhile, the magnitude of the contribution of tropical sea surface temperature (SST) to TPSC is different based on observations and simulations. Observations indicate that TPSC is insensitive to El Niño/La Niña events, whereas the simulated ensemble mean TPSC is correlated strongly with Niño 3.4 SST index. In El Niño years, higher specific humidity and more numerous synoptic disturbances are found around the Tibetan Plateau. As several ensemble members show features close to those observed, the observed insensitivity of TPSC to El Niño–Southern Oscillation (ENSO) events is considered attributable to the limited sample size of the observations. This is corroborated in the analysis for a relatively short period, in which the observed TPSC is sensitive to ENSO. Comparison of the results of the historical simulations with those of the simulations without warming suggests that global warming has reduced the snow‐to‐rain ratio over the Tibetan Plateau, which is compensated by the overall increase in precipitation. Consequently, the impact of global warming on TPSC was negligibly weak until the 2000s. Key Points: Contributions of Arctic Oscillation (AO) and El Niño–Southern Oscillation (ENSO) to winter snow cover over the Tibetan Plateau are investigated The simulated snow cover is linked weakly to AO and strongly to ENSO unlike those suggested by observations Combined impact of negative AO and La Niña reduces snow cover over the Tibetan Plateau